SIAPA YANG MENGAMBIL MANFAAT DARI PELAYANAN KIA DI INDONESIA TIMUR? ANALISIS DATA SDH 1991* - Mubasyir Hasanbasri (Populasi, 1993)
Maternaland Child Health (MCH) program has been an important national policy measure to prevent child death and to promote child health. In consideration of government restricted budget, the size of and spreadity of Indonesian population, government has provided at least one health center for every subdistrict and has promoted community participation through community based health post to reach the out reach population. This study seeks to explore community's utilization of this program and assesses whether the program has reached the priotity target groups such as the children with uneducated mothers and lower economic status. The 1991 Indonesian Demographic and Health Survey data is used and sampel of 860 children of 12-23 month old from eastern Indonesiaisthe focus of analysis. Logistic regression is used as multivariate analysis. The resultshows that the MCH program seems to have solved accessibility problem of economic constraint, however, contrary to the high priority groups being targeted, lower educated mothers use less services than those of more educated. This may be associated with lack of appropriate local conceptual framework in understanding preventive health behaviour among uneducated mothers and less progressive efforts in enforcing the need for social participation from the uneducated mothers.